Two-way metalinear PC grammar systems and their descriptional complexity - Meduna Alexander (2004)
Besides a derivation step and a communication step, a two-way PC grammar system can make a reduction step during which it reduces the right-hand side of a context-free production to its left-hand side. This paper proves that every non-unary recursively enumerable language is defined by a centralized two-way grammar system, ┌, with two metalinear components in a very economical way. Indeed, ┌'s master has only three nonterminals and one communication production; furthermore, it produces all sentential forms with no more than two occurrences of nonterminals. In addition, during every computation, ┌ makes a single communication step. Some variants of two-way PC grammar systems are discussed in the conclusion of this paper.
Keywords: Természettudományok; Számítás- és információtudomány